How did the Good School Toolkit reduce the risk of past week physical violence from teachers to students? Qualitative findings on pathways of change in schools in Luwero, Uganda. (May 2017) - Kyegombe, N.; Namakula, S.; Mulindwa, J.; Lwanyaaga, J.; Naker, D.; Namy, S.; Nakuti, J.; Parkes, J.; Knight, L.; Walakira, E.; Devries, K.M.
Abstract: Violence against children is a serious violation of children's rights with significant impacts on current and future health and well-being. The Good School Toolkit (GST) is designed to prevent violence against children in primary schools through changing schools' operational cultures. Conducted in the Luwero District in Uganda between 2012 and 2014, findings from previous research indicate that the Toolkit reduced the odds of past week physical violence from school staff (OR = 0.40, 95%CI 0.26–0.64, p < 0.001), corresponding to a 42% reduction in risk of past week physical violence. This nested qualitative study involved 133 interviews with students, teachers, school administration, and parents, and two focus group discussion with teachers. Interviews were conducted using semi-structured tools and analysed using thematic analysis complemented by constant comparison and deviant case analysis techniques. Within a context of normative acceptance of corporal punishment this qualitative paper reports suggestive pathways related to teacher-student relationships through which reductions in violence operated. First, improved student-teacher relationships resulted in improved student voice and less fear of teachers. Second, the intervention helped schools to clarify and encourage desired behaviour amongst students through rewards and praise. Third, many teachers valued positive discipline and alternative discipline methods, including peer-to-peer discipline, as important pathways to reduced use of violence. These shifts were reflected in changes in the views, use, and context of beating. Although the GST is effective for reducing physical violence from teachers to students, violence persisted, though at significantly reduced levels, in all schools with reductions varying across schools and individuals. Much of the success of the Toolkit derives from the support it provides for fostering better student-teacher relationships and alternative discipline options. Such innovation could usefully be incorporated in teacher training syllabi to equip teachers with knowledge and skills to maintain discipline without the use of fear or physical punishment. Highlights: Evaluates reduction of violence from teachers to students using Good School Toolkit. Reduced fear of teachers is important for students' learning and participation. Peer discipline valuable for improving behaviour and reducing disciplining by teachers. Positive discipline helps to clarify and encourage desired behaviour from students. Highlights potential of new norms supportive of meaningful teacher-student relationships.